(untitled) - Fraval, Simon (Netherlands, 2019)
Members of rural households in sub-Saharan Africa (SSA) are both vulnerable to the health burdens that stem from food insecurity and central to improving the availability and affordability of wholesome foods. It has been estimated that chronic and hidden hunger can be alleviated by implementing a suite of nutrition-specific interventions at a cost of US\
Keywords: Nông nghiệp,Agriculture; Khía cạnh kinh tế,Economic aspects